Kilka uwag o prawniczych studiach II stopnia w latach 1952–1954 - Olszewski, Henryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article is an analysis of graduate law programmes at Polish universities in 1952–1954. Drawing on the literature and sources, the author examines the changes taking place in the education of lawyers during the period of Stalinist indoctrination. He analyses the two-tier programme of studies and concludes that despite its political connotations the programme was not without some achievements. The most important among them was that it educated avaluable generation of law historians making up for the losses suffered by the profession during the Second World War and in the first few years after it ended.
Keywords: prawo w totalitaryzmie; edukacja prawników; historia prawa